Effectivity of karamunting Melastoma malabathricum leaves in inhibiting ovarian development of Nile tilapia Oreochromis niloticus - Yogo Tri saloko; Muhammad Agus Suprayudi; Muhammad Zairin Jr. (Jurnal Akuakultur Indonesia)
ABSTRACT